2017
DOI: 10.1038/nature22342
|View full text |Cite
|
Sign up to set email alerts
|

Blocking FSH induces thermogenic adipose tissue and reduces body fat

Abstract: Menopause is associated with bone loss and enhanced visceral adiposity. We have shown previously that a polyclonal antibody (Ab) to the β-subunit of the pituitary hormone Fsh increases bone mass in mice. Here, we report that this Ab sharply reduces adipose tissue in wild type mice, phenocopying genetic Fshr haploinsufficiency. The Ab also causes profound beiging, increases cellular mitochondrial density, activates brown adipose tissue, and enhances thermogenesis. These actions result from the specific binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
280
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 281 publications
(304 citation statements)
references
References 55 publications
(81 reference statements)
14
280
3
Order By: Relevance
“…One of our laboratories (M.Z.) recently published the surprising finding that the pituitary hormone FSH (follicle‐stimulating hormone) is related to both osteoporosis and obesity . A reproductive hormone, FSH, had not previously been implicated in adipocyte biology.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…One of our laboratories (M.Z.) recently published the surprising finding that the pituitary hormone FSH (follicle‐stimulating hormone) is related to both osteoporosis and obesity . A reproductive hormone, FSH, had not previously been implicated in adipocyte biology.…”
mentioning
confidence: 99%
“…M.Z. generated a polyclonal antibody that blocked FSH action on its receptor, and in doing so not only prevented bone loss but also caused a dramatic reduction in body fat and a conversion of white to beige adipose tissue in various murine models of obesity . Because the latter results were particularly novel and unexpected, instead of moving directly to publish the findings, M.Z.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another protein associated with osteoporosis and adiposity is the follicle‐stimulating hormone (FSH) . Interestingly, a recent report by Zaidi and colleagues showed that blocking FSH function with a polyclonal antibody potently activates brown/beige fat thermogenesis and alleviates osteoporosis and visceral adiposity in mice (Liu et al, ).…”
Section: Proteins/peptidesmentioning
confidence: 99%
“…The follicle‐stimulating hormone receptor (FSHR), an important member of the glycoprotein hormone receptor (GPHR) subfamily of the G protein‐coupled receptor (GPCR) superfamily, is necessary for the action of FSH, an important component of the hypothalamic–pituitary–gonadal axis (Jiang et al, ; Liu et al, ). Similar to other glycoprotein hormones such as luteinizing hormone (LH) and thyroid‐stimulating hormone (TSH), FSH is also composed of two non‐covalently associated α and β subunits.…”
Section: Introductionmentioning
confidence: 99%